Суспільно-географічна оцінка конфесійного простору Рівненської області - Костащук, Іван; Kostaschuk, Ivan (My University, 2017)
У статті проведено суспільно-географічний аналіз конфесійного простору Рівненської області, а саме: простежено територіальні особливості конфесійного простору та виконано порівняльно-географічний аналіз у різних адміністративно-територіальних районах, розкрито загальні риси географії релігійних конфліктів, які відбуваються в останні роки у зв’язку з переходом громад від УПЦ до УПЦ КП; апробовано методику визначення релігійної активності та забезпеченості населення громадами різних конфесій, напрямів і течій, що зареєстровані й виконують свою діяльність на території досліджуваного регіону. A socio-geographical analysis of the confessional space of Rivne region has been carried out in this article, namely: the territorial features of the confessional space have been traced and a comparative-geographic analysis has been carried out in various administrativeterritorial districts; general features of the geography of religious conflicts that have taken place in recent years in connection with the transition of communities from the UOC to the UOC-KP have been analyzed; the methodology for determining religious activity and availability to the population of communities of different denominations, directions and trends registered and operating in the territory of the region under study has been tested. The article also presents the structure of the religious space, to which we refer to the confessional space, atheists, agnostics and akirkhs. Important attention is paid to the analysis of the indicators of availability of religious communities to the population, namely the number of religious communities per 10 000 people and the size of the population belonging to one religious community. The article also calculates the coefficient of religious mosaic.
Social-Geographic Assessment of the Confessional Space of Rivne Region
Keywords: конфесійний простір; релігійна активність населення; Волинь; індекс релігійної мозаїчності; православний підпростір; католицький підпростір; протестантський підпростір, іудейський підпростір, язичницький підпростір; confessional space; religious activity of the population; Volyn; index of religious mosaic; Orthodox subspace; Catholic subspace; Protestant subspace; Jewish subspace; pagan subspace; іудейський підпростір; язичницький підпростір